Caracterização de filmes biopoliméricos à base de biomassa de banana verde e sua avaliação para produção de cápsulas - Siqueira , Luana Volkmann (2022)
Banana is one of the most consumed fruits of the world, both in its fresh and processed form: Green banana is a source of B-complex vitamins (B1, B6) and a high amount of resistant starch (RA), with similar behavior to dietary fibers in the gastrointestinal tract: the essay aimed to evaluate biodegradable films produced with the biomass of green banana pulp in different concentrations, plus sorbitol and propylene glycol in different proportions; to evaluate its properties and its capacity for the production of vegetarian capsules, the films produced by the solvent evaporation technique "casting" in an oven were rated, for macroscopic properties, thickness, water vapor transmission rate (TVA), swelling index, mechanical properties, and applicability for the development of capsules: Biomass proved to be an excellent material for the formulation of biofilms, as it is a raw material from a renewable source, the biomass-based films were rated, according to the desirable factors: low TVA, mechanical strength, good flexibility, transparency, low swelling index, and lower thickness, the biomass-based film these characteristics: the biopolymeric films produced with sorbitol and banana biomass presented low opacity, high malleability, and high homogeneity. In agreement with the XRD analysis, it was possible to verify that the evaluated films are predominantly amorphous.